Methane Conversion to Liquid Hydrocarbons over W-ZSM-5 and W Loaded Cu/HZSM-5 - Anggoro, Didi Dwi; Amin, Nor Aishah Saidina (ASEAN Journal of Chemical Engineering, 2006)
The direct conversion of natural gas-in particular, its principal component, methane into useful products has been the subject of intense study over the past decades. However, commercialization of this process is still not viable because its conversion and selectivity potentials remain low. Thus, the search continues to come up with a suitable catalyst that allows methane to be oxidized in a controlled environment to yield a high percentage of higher hydrocarbons. ZSM-5 zeolite has been known to be a suitable catalyst for olefin oligomerization. Previous studies, however, have indicated that ZSM-5 zeolites are not resistant to high temperatures. In this work, ZSM-5 was modified with copper and tungsten to develop a highly active and heat-resistant bifunctional oxidative acid catalyst. The oxidation of methane was performed over W/Cu/HZSM-5 catalyst and the results compared with the catalytic performance of W/ HZSM-5 and HZSM-5 catalysts. The metal oxide on the catalyst surface led to enhanced conversion of Hz and CO to CZ-3 ydrocarbons and, hence, reduced HzO selectivity. Inh the liquid hydrocarbons, Cs+ selectivity increased with increasing amount of surface Bn1Jnstedacid sites. The experimental results indicated higher methane conversion and liquid hydrocarbon selectivity than that of W/3.0Cu/HZSM-5 catalyst.